Positron emission tomography and reframing vasculitis as a spectrum of disease when investigating a patient with a fever of unknown origin. (19th September 2018) - Shahi, Farah; Samson, Anda
Abstract : A retired businessman presented to the infectious diseases department with a history of ongoing fevers and myalgia and raised inflammatory markers. This continued despite adequate antibiotic treatment of an epididymo-orchitis. Extensive investigations, including bone marrow and liver biopsies and a positron emission tomography, did not reveal a cause but showed reactive change in the bone marrow. Later, he developed a vasculitic rash and vision loss due to non-arteritic anterior ischaemic optic neuropathy. High-dose steroids were immediately initiated. A temporal artery biopsy was performed, which confirmed a healing large vessel vasculitis, possibly giant cell arteritis. He has responded very well to therapy. We must better appreciate the limitations of positron emission tomography in investigating a fever of unknown origin. The case also encourages awareness of autoimmune disorders as the leading category of causative diseases for this in older age groups.